TV-Based Learning in Bangladesh : Is it Reaching Students? - Biswas, Kumar (World Bank, Washington, DC, 2020)
Is TV-based learning during COVID-19 school closures in Bangladesh reaching students? Most students (86 percent) within our sample of more than 2,000 Grade 9 stipend recipients are aware of government provided TV-based learning programs; yet only half of the students with access to these programs choose to access them. Also, very few students (21 percent) have access to government provided online learning programs, and among those that do, only about 2 percent choose to access them. There is a perceptible decline in the time students spend studying at home after school closures. This may be linked to the fact that 1 in 2 parents claim they are unable to help their children with new topics. Despite lower education, mothers are significantly more likely to be involved in the child’s education compared to fathers. Most students (90 percent) claim they have a supportive environment at home for studying. This is true for both boys and girls. Finally, nearly 65 percent of households in our sample report declines in income and 28 percent had to decrease the amount of food consumed within the household in the previous week.